E-MERLIN Radio Continuum Measurements of OB Star Winds in CYG OB2. Issue Volume 12:Issue S316(2015) (31st March 2017) - Morford, Jack; Prinja, Raman; Fenech, Danielle
Abstract: Here, we report on the first results from the e-MERLIN Cyg OB2 Radio Survey (COBRaS), which is designed to exploit e-MERLIN's enhanced capabilities to conduct deep-field mapping of the tremendously rich Cyg OB2 association. The project aims to deliver the most detailed radio census of the most massive OB association in the northern hemisphere. There exists considerable evidence for clumping in the winds of hot stars, which has hugely important consequences for mass-loss determinations. The amount of mass lost from a massive star is a crucial parameter required for stellar and cluster evolution models that are paramount to our understanding of the formation and evolution of massive star clusters. Presenting some of the first 20cm (L band) detections of massive stars in Cyg OB2, both accurate mass-loss determinations and constraints upon clumping within their winds are made. These data substantially increase the observational detections of the outer wind of massive stars and in combination with other observations at different wavelengths, COBRaS will greatly advance our knowledge of clumping as a function of radial distance around massive stars.